1994
DOI: 10.1007/bf01711902
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia furfur-related colonization and infection of central venous catheters

Abstract: The incidence of Malassezia furfur-related colonization of central venous catheters appears to be low but not negligible, which warrants the use of specific culture techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…44 Notably, current routine methods for yeast identification may be insufficient to identify isolates of lipophilic Malassezia species, which have been found to be associated to a low but not negligible extent with infection of central venous catheters for parenteral nutrition-bearing lipid emulsions. 45 Alpert et al 46 reported Malassezia furfur fungemia in infancy, including a patient with evidence of endocarditis. In addition, Aspergillus species frequently found in patients after cardiovascular surgery account for a high percentage of fungal IEs.…”
Section: Discussionmentioning
confidence: 99%
“…44 Notably, current routine methods for yeast identification may be insufficient to identify isolates of lipophilic Malassezia species, which have been found to be associated to a low but not negligible extent with infection of central venous catheters for parenteral nutrition-bearing lipid emulsions. 45 Alpert et al 46 reported Malassezia furfur fungemia in infancy, including a patient with evidence of endocarditis. In addition, Aspergillus species frequently found in patients after cardiovascular surgery account for a high percentage of fungal IEs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of specific antibody (IgE) to Malassezia antigens in affected patients who respond to azole antifungals. 24,25 Here it is most often associated with intravenous lipid supplementation. 21 Confluent and reticulate papillomatosis 22 is a rare condition affecting the upper trunk where patients develop a linear network of scaly lesions.…”
Section: Other Conditionsmentioning
confidence: 99%
“…The isolation of Malassezia furfur and M. sympodialis from catheter samples in ICU patients is signifi cant as they have been ascribed a role in fungemia in pediatric patients with parental lipid hyperalimentation [35][36][37] . Susceptibility tests for yeasts have not been standardized to date, nevertheless it is important to introduce changes in the current laboratory methodology in order to enable their isolation, avoiding underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%